2020
DOI: 10.1021/acs.jpcc.0c05380
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Improving the Kinetics of Bulk Carbonation on Sodium Carbonate

Abstract: Slow kinetics of CO2 capture on sodium carbonate (Na2CO3) restricts its application in CO2 capture from flue gas despite advantages of low cost, high abundance, and economical retrofitting of extant power plants. Surface carbonation on Na2CO3 is facile; hence, the observed slow kinetics is likely due to diffusion limitations. We present an atomic-level study of the kinetics of Na2CO3 bulk carbonation. We proposal two possible pathways: the molecular interstitial diffusion (MID) mechanism, where CO2 and H2O dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…After nine regenerations, the reaction rate constant of NaCH-923 was 5.30 × 10 –2 min –1 (Figure S5b). Cai et al reported that this situation may be the result of a series of special diffusion reactions occurring at the interface between sodium carbonate and sodium bicarbonate . The reaction rate is likely to increase with the number of cycles.…”
Section: Resultsmentioning
confidence: 99%
“…After nine regenerations, the reaction rate constant of NaCH-923 was 5.30 × 10 –2 min –1 (Figure S5b). Cai et al reported that this situation may be the result of a series of special diffusion reactions occurring at the interface between sodium carbonate and sodium bicarbonate . The reaction rate is likely to increase with the number of cycles.…”
Section: Resultsmentioning
confidence: 99%
“…For the sake of convenience, the two species mentioned above are abbreviated as NaO x . The formation of sodium carbonate or hydroxide species is unlikely, since in that case, the Na 1s would appear at a considerably lower BE [39]. When the catalyst is exposed to CO 2 :H 2 (Figure 2d), an evident shoulder appears at the low BE side of the Na 1s peak.…”
Section: Chemical State Measured In H 2 and Co 2 :H 2 Gas Atmospheresmentioning
confidence: 97%
“…They found that the sorbent loaded with γ-Al 2 O 3 as the carrier offers several advantages, such as good dispersion of the active component, easy availability of raw materials, and high adsorption efficiency. Cai et al 21 explored the kinetics of the sodium carbonate intrinsic carbonation reaction and proposed effective improvements. Kazemi et al 22 enhanced the adsorption capacity of the sorbent by modifying the specific surface area and pore volume of γ-Al 2 O 3 carriers.…”
Section: Introductionmentioning
confidence: 99%